Inner Ear Malformations in Congenital Deafness Are Not Associated with Increased Risk of Breech Presentation. (2nd November 2021) - Sekulic, Slobodan; Lemajic-Komazec, Slobodanka; Sokolovac, Ivana; Topalidou, Anastasia; Gouni, Olga; Petkovic, Branka; Martac, Ljiljana; Kekovic, Goran; Redzek-Mudrinic, Tatjana; Capo, Ivan
Abstract: Background There is speculation that an immature vestibular system may be associated with breech presentation at delivery. Our aim was to determine whether syndromes with congenital inner ear malformations were accompanied by a higher frequency of breech presentation/malpresentations than in the general population (2%−3%). Methods: A review was conducted for published literature using PubMed/MEDLINE (1936–2016), to determine frequency of breech presentation and transverse lie in cases with congenital deafness (Michel aplasia, Wildervanck syndrome, Mondini-Alexander dysplasia, Waardenburg syndrome, CHARGE syndrome, Large vestibular aqueductal syndrome, Pendred syndrome, Oculo-aurico-vertebral spectrum, Jervel and Lange-Nielsen syndrome, Usher syndrome, and Scheibe dysplasia) and vestibular nerve aplasia. Results: Identified were total of 122 cases. The frequency of breech presentation was 1.64%, and of transverse lie 1.64%, giving a total of 3.28% malpresentations. Conclusion: The results of the study suggest that congenital malformations of the vestibular apparatus are not associated with the increased risk of breech presentation at delivery.